Escalonamento de Aplicações em Instâncias Preemptivas Sujeitas a Falhas Temporais - Teylo, Luan; Drummond, Lucia M. A.; Arantes, Luciana; Sens, Pierre (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2019)
By contracting Virtual Machines on Amazon EC2, the user can opt for on-demand instances, which have high availability, or instances spot (preemptive), which are idle resources offered at a lower price, whose availability may vary throughout the run. Despite the economic advantage, if the demand for resources increases, the preemptive instances can be revoked by the provider without warning, and put in hibernation until the demand decreases. This work presents initial results and the formulation of the scheduling problem which considers hibernation-prone preemptive instances to minimize the monetary cost of execution.